Safety issues in Marine Parks - Ramli, Azahari; Aziz, Zulkufli; Ismail, Mohd Azril; Mustafa, Munauwar; Ahmad, Shuhymee; Talib, Jeffry Azhar (2015)
The case is about safety issues of the Pulau Lara Marine Park. Safety is a paramount concern of anyone as lack of safety awareness and implementation will expose the operators, the authority and particularly the tourists in danger. A study has been done to tour operators and the results were analysed.As the result shown the high awareness of safety climate, further constructive actions should be implemented to increase or maintain the safety climate among the tour operators.This case is best suited to BPMH 3033 Occupational Safety & Health which is compulsory course for student from Bachelor Degree of Human Resource Management.